2022
DOI: 10.1002/dac.5181
|View full text |Cite
|
Sign up to set email alerts
|

High gain miniaturrized super‐wideband microstrip patch antenna

Abstract: A miniaturized super-wideband (SWB) monopole antenna is presented in this work. Electrical dimension of the presented antenna is 0.239λ Â 0.239λ Â 0.0147λ, where λ indicates the wavelength corresponding to the lowest operating frequency. Presented antenna displays single À10 dB operating band from 2.75 to 28 GHz with 164% percentage bandwidth and bandwidth ratio of more than 10:1. The proposed SWB antenna exhibits a large bandwidth dimension ratio (BDR) of 2871 with realized gain of 4.80 dBi. Radiating patch o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…To widen the operating bandwidth of microstrip antennae, many efforts have been exerted by the publishers taking into consideration the size miniaturization, complexity minimization, and cost reduction. Different techniques have been addressed to meet the desired requirements and some of these techniques are partial ground plane [ 6 , 7 , 8 ], electromagnetic band gap (EBG) ground structure [ 9 ], loaded rectangular and annular notches in the ground plane [ 10 , 11 , 12 ], radiator ring slot and shorting vias [ 13 ], parasitic elements [ 14 ], and electrostrictive effect [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To widen the operating bandwidth of microstrip antennae, many efforts have been exerted by the publishers taking into consideration the size miniaturization, complexity minimization, and cost reduction. Different techniques have been addressed to meet the desired requirements and some of these techniques are partial ground plane [ 6 , 7 , 8 ], electromagnetic band gap (EBG) ground structure [ 9 ], loaded rectangular and annular notches in the ground plane [ 10 , 11 , 12 ], radiator ring slot and shorting vias [ 13 ], parasitic elements [ 14 ], and electrostrictive effect [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Furthermore, the need for wide bandwidth in the ultrawideband (UWB) range and improved gain will keep increasing as we integrate various high frequency applications with high data rates into a single device. 4,5 An antenna is an indispensable part of wireless communications devices. Designing an antenna for future wireless devices is challenging for researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Modern wireless communications are growing at a rapid pace where the devices used in communication systems a few years back were required to be very compact and suitable for multiband operations, but nowadays the demand for bandwidth enhancement is in the field of prime interest 1–3 . Furthermore, the need for wide bandwidth in the ultra‐wideband (UWB) range and improved gain will keep increasing as we integrate various high frequency applications with high data rates into a single device 4,5 . An antenna is an indispensable part of wireless communications devices.…”
Section: Introductionmentioning
confidence: 99%
“…[9]. Ample research has been reported for different microstrip patch antenna geometries in a number of studies [10][11][12][13][14][15][16][17][18][19][20] In this article, a microstrip patch antenna with a U-shaped patch and a paper-based substrate is designed. Aluminum is utilized for the metallic parts including the patch, ground plane and microstrip line, which is used for feeding.…”
Section: Introductionmentioning
confidence: 99%